Author Guidelines - Guidelines, Author; Pontificia Universidad Javeriana (2013)
Reproduction Rights Universitas Scientiarum is licensed under Creative Commons: Attribution - Noncommercial - No derivative works, 2.5 of Colombia. Consequently, it can be electronically reproduced, distributed and publically communicated, provided the authors and the Pontificia Universidad Javeriana are acknowledged. Commercial use of this work is not permitted. Modifications to the original work, and distribution of modified copies are prohibited. Upon acceptance of the article, the author will send the journal’s Office a printed and signed license of economic rights transfer, which authorizes its reproduction in Universitas Scientiarum (the license can be downloaded from the journal website; http://revistas.javeriana.edu.co/scientarium/web; http://revistas.javeriana.edu.co/scientarium/ojs). Such permission will infer the author’s acceptance of the article’s dissemination not only on paper but also in electronic media, that is, in websites and in national and international bibliographic databases. The magazine accepts pre-print articles, previously uploaded to e-print servers (OAI - such as arxiv.org).